SAR Absolute Radiometric Calibration Utilizing Offshore Wind Farms With Mask-Based Response Energy Extraction Approach - Yongsheng Zhou; Qian Ying; Qiang Yin; Aichun Wang; Fan Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The absolute radiometric calibration of synthetic aperture radar (SAR) using natural point targets holds significant potential. Current natural point targets for calibration are often insufficiently concentrated within a single imaging scene, leading to calibration uncertainty. These targets also exhibit non-ideal point-like characteristics in SAR images, while existing methods for their response energy extraction rely on the assumption of ideal point targets. Given that offshore wind farms typically consist of numerous windmills with point-target attributes and high signal-to-clutter ratio (SCR), this article proposes a radiometric calibration method using offshore wind farms, which can monitor the stability of calibration constants or correct the calibration constants due to sensor performance degradation. First, a method for selecting offshore wind farms is developed, tailored to radiometric calibration. Since not all windmills within a farm are suitable for calibration, a windmill selection method based on SCR and radar cross-section (RCS) stability is formulated, with the true RCS of the windmills statistically determined using historical SAR data. To overcome the limitations of traditional response energy extraction methods, a mask set is introduced to identify the shape and energy distribution of offshore windmills in SAR images. Finally, the radiometric calibration constant is determined using the response energy calculated using the proposed method and the true RCS of offshore windmills. Experimental results using Sentinel-1 data validate the effectiveness of the method, with the obtained calibration constant deviating from the nominal calibration constant within a range of 0.01–0.71 dB.